If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3x = 4x + -4 Combine like terms: 2x + 3x = 5x 5x = 4x + -4 Reorder the terms: 5x = -4 + 4x Solving 5x = -4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5x + -4x = -4 + 4x + -4x Combine like terms: 5x + -4x = 1x 1x = -4 + 4x + -4x Combine like terms: 4x + -4x = 0 1x = -4 + 0 1x = -4 Divide each side by '1'. x = -4 Simplifying x = -4
| (3+5)(2m-8)=0 | | 4x4y3/12x1y2 | | 6(12)+6n-70-4n=8 | | 22613.85=x+(x*.0825) | | 4x+9=-20 | | 23h-67=-44 | | (12x-6)+(16-5x)= | | 12x+3y+120=180 | | 7-4.5= | | 3(2r+6)=24 | | 9(2x+6)= | | 5d-c=12 | | 8(9x+9)+9(11-x)= | | (4x+1)+(11-4x)= | | 35+50x= | | (4x+13)+(8x-5)= | | 7(8x+5)= | | 3x-5x=-9+x | | 2x^4+7=47 | | 2a+7b-3b+a= | | m+50x=35 | | f(x)=-16x+160x | | 6x+x-8=6x+5 | | 3.2=125x | | 8m-2m=72 | | 5g-5=7 | | -5=-19-n/7 | | 13x-60=83 | | x^6+7x^5+2x^4+9x^3+10x^2-12x-15=0 | | 2/5(x-15)=500 | | c/7+5=-6 | | 24k^2=-24k |